Capillary damage in skeletal muscle in advanced Chagas? disease patients - Torres, SoniaH; Finol, H ctorJ; Montes de Oca, Mar a; V squez, Francia; Puigb, JuanJ; Loyo, Jos G. (Parasitology research (1987), 2004)
The damage to skeletal muscle capillaries in advanced Chagas' disease (stages II and III) was investigated in the vastus lateralis muscle of six patients and compared to that of six normal subjects. Capillaries were visualized by the PAS-amylase reaction and muscle fibres were classified by the ATPase histochemical method. Transmission electron microscopy was used to look for capillary alterations. The capillary-to-fibre ratio and number of capillaries adjacent to type I and type IIa fibres were decreased in the patient group. At the ultrastructural level, all patients showed capillary abnormalities, mainly basement membrane thickening and reduplication, capillary occlusion, proliferative endothelial cell cytoplasm with dense bodies, large vacuoles, altered mitochondria and prominent rough endoplasmic reticulum, as well as pericyte abnormalities. Capillary alterations are similar to those in patients affected by autoimmune diseases, suggesting an autoimmune component in the chronic phase of this disease. The reduction in capillarity may contribute to altered muscle performance in these patients.